Pengabdian PEMBERDAYAAN MASYARAKAT MELALUI PEMANFAATAN AMPAS KOPI DAN CENGKEH SEBAGAI AROMATERAPI ANTI NYAMUK - Wita Hariani; Yohanes Susanto; Kasman; Shinta Wiji Rahayu (Jurnal Pengabdian, 2026)
This community service program aims to enhance community capacity, independence, and welfare through the utilization of coffee grounds waste and cloves as an environmentally friendly and economically valuable mosquito-repellent aromatherapy product. The main problems faced by the community include high dependence on chemical-based mosquito repellents, which may pose negative impacts on health, and the low utilization of household waste that is often considered to have no value. The implementation method employs a community empowerment approach through several stages, including problem identification, socialization, product manufacturing training, and continuous assistance. This activity involves active community participation in a practice-based learning process, ranging from processing coffee grounds, mixing clove ingredients, to packaging aromatherapy products. Evaluation was conducted through pre-tests and post-tests, as well as observation of changes in participants’ knowledge and skills. The results show an increase in community knowledge by approximately 85% and improved skills in independently producing aromatherapy products. In addition, a small business group based on natural resource utilization was established, which has the potential to be developed as an additional source of income. This program not only contributes to improving environmental health through the use of natural materials but also strengthens the economic and social empowerment of the community. Therefore, this community service activity can serve as a sustainable model of community empowerment innovation based on local potential.